Assessing and managing patients with borderline personality disorder requesting medical assistance in dying - Links, Paul S.; Aslam, Hira; Brodeur, Jonah (Frontiers in Psychiatry, 2024)
Background: When physician assisted dying (referred to as Medical Assistance in Dying or MAiD in this article) is available for individuals with mental disorders as the sole underlying medical condition (MD-SUMC), patients with borderline personality disorder (BPD) frequently request MAiD. Psychiatrists and other clinicians must be prepared to evaluate and manage these requests. Objectives: The purposes of this paper are to define when patients with BPD should be considered to have an irremediable, treatment resistant disorder and provide clinicians with an approach to assess and manage their patients with BPD making requests for MAiD. Methods: This perspective paper developed the authors' viewpoint by using a published, authoritative definition of irremediability and including noteworthy systematic and/or metaanalytic reviews related to the assessment of irremediability. Results: The clinician must be aware of the eligibility requirements for granting MAiD in their jurisdiction so that they can appropriately prepare themselves and their patients for the